2017
DOI: 10.5195/palrap.2017.155
|View full text |Cite
|
Sign up to set email alerts
|

Online Appointment-Scheduling for Optimizing a High Volume of Research Consultations

Abstract: Librarians at Penn State University piloted the online appointment-scheduling tool YouCanBook.me to determine its effectiveness in facilitating a high number of research consultations and improving an embedded service model. Librarians sought to leverage the tool to work with as many students as possible while balancing other duties. This article details using YouCanBook.me for this specific application, provides data and evaluation of the pilot, and explores possibilities for scaling usage of this scheduling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Several studies have evaluated the amount of time spent by librarians on patron interactions in a variety of formats ( Attebury et al, 2009 ; Gale & Evans, 2007 ; Lederer & Feldmann, 2012 ; Spencer & Dorsey, 1998 ; Yi, 2003 ). Time spent is often a particularly important measure when determining whether a reference service or initiative can scale, although use of scheduling tools, patron-initiated appointment models, and other management strategies can mitigate workload problems associated with interaction length or improve otherwise improve scalability by decreasing some of the logistical burdens on librarians ( Cole & Reiter, 2017 ; Hess, 2014 ; Hoskisson & Wentz, 2001 ; Newton & Feinberg, 2020 ; Reiter & Cole, 2019 ). Magi and Mardeusz (2013) note that individual research consultations increase the likelihood that interactions based on complex or difficult questions will be rewarding because they “give students and librarians more time and space” compared to more perfunctory exchanges in person or online.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have evaluated the amount of time spent by librarians on patron interactions in a variety of formats ( Attebury et al, 2009 ; Gale & Evans, 2007 ; Lederer & Feldmann, 2012 ; Spencer & Dorsey, 1998 ; Yi, 2003 ). Time spent is often a particularly important measure when determining whether a reference service or initiative can scale, although use of scheduling tools, patron-initiated appointment models, and other management strategies can mitigate workload problems associated with interaction length or improve otherwise improve scalability by decreasing some of the logistical burdens on librarians ( Cole & Reiter, 2017 ; Hess, 2014 ; Hoskisson & Wentz, 2001 ; Newton & Feinberg, 2020 ; Reiter & Cole, 2019 ). Magi and Mardeusz (2013) note that individual research consultations increase the likelihood that interactions based on complex or difficult questions will be rewarding because they “give students and librarians more time and space” compared to more perfunctory exchanges in person or online.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An unanticipated finding from this research was the often significant time lapse between students attending a consultation and implementing this knowledge with their research activities. In retrospect this is unsurprising as given IRC's labour-intensive nature Evaluating a recorded appointment service and scheduling limitations; many students may struggle to request consultations at the point of need (Kuglitsch et al, 2017;Cole and Reiter, 2017). Thus a need exists to develop and evaluate strategies to support effective knowledge recall and transfer.…”
Section: Discussionmentioning
confidence: 99%
“…This gap in the literature perhaps is revealing of librarians’ attitudes toward this aspect of our profession – though most accept its importance (Magi and Mardeusz, 2013; Fields, 2006), this is not reflected in the time and attention being paid to a critical consideration of how librarians conceptualize, communicate about and ensure access to one-on-one support for students’ research. An exception to this general inattention to appointment no-shows is found in the work of Cole and Reiter (2017), who found that roughly 5% of research appointments made at their institution resulted in no-shows.…”
Section: Literature Reviewmentioning
confidence: 99%